A "heart" in the desert. Inquiries about the urban proposal of Villa el Chocón in Argentine Patagonia (1968/1972) - Parera, Cecilia (Universidad ORT Uruguay, 2019)
In the fifties and sixties of the twentieth century, a disciplinary critique of the existing city was disseminated, rejecting the functionalist postulates applied in the inter-war, for the benefit of careful readings of the phenomenological perception of space, the mixture of uses and the human scale The present article pretends to investigate around this change of disciplinary paradigm, adopting the Villa el Chocón in the Argentinian Patagonia, and particularly the proposal for its civic center, as the main case of study, being that this small town puts in evidence a new approach regarding project strategies in urban and architectural matters. In particular, the hypothesis that guides the paper raises a conceptual proximity of the authors of the aforementioned work with the postulates that supported the distancing of the so-called Modern Movement, as well as an adherence to the motto “the heart of the city”, issues debated in Europe since the early 1950s. In attention to the stated objectives, the historical-critical analysis of the selected case made it possible to identify these affinities, differentiated as much from rationalism as the predominant strategy until the outbreak of the Second World War, as well as the subsequent systemic and indeterminate approach that would characterize a large part of the architectural production of the 1970s in Argentina.